2001
DOI: 10.1037/0022-0167.48.3.274
|View full text |Cite
|
Sign up to set email alerts
|

American Indian perspectives on the career journey.

Abstract: This exploratory qualitative study was conducted to examine the meaning of career and related concepts for adult American Indians. Eighteen Northern Plains American Indians were interviewed, and the resulting data were analyzed using consensual qualitative research strategies (C. E. Hill, B. J. Thompson, & E. N. Williams, 1997). Five major topic areas emerged from the data: the meaning of career, definitions of success, supportive factors, obstacles, and living in 2 worlds. Within these domains, several catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
109
2
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(127 citation statements)
references
References 20 publications
10
109
2
3
Order By: Relevance
“…In the only study to assess the consensus process, Juntunen et al (2001) listened to audiotapes of data analysis meetings and determined that each team member shared opinions and that there was equitable discussion before reaching consensus.…”
Section: The Consensus Processmentioning
confidence: 99%
“…In the only study to assess the consensus process, Juntunen et al (2001) listened to audiotapes of data analysis meetings and determined that each team member shared opinions and that there was equitable discussion before reaching consensus.…”
Section: The Consensus Processmentioning
confidence: 99%
“…Moreover, Aboriginal and Torres Strait Islander students reported that their experiences at universities increased their ability to contribute to their welfare of their community (a vital motivator for their college-going journey); yet, they indicated that the university did not provide support to help them cope with responsibilities such as family obligations (Asmar et al 2014). Canadian First Nations students define success in terms that coincide with the relational dimensions of family and community (Juntunen et al 2001). Understanding the lives of First Nations post-secondary students, including the awareness of their extended family obligations, was found to be a crucial strategy for facilitating success for those students (Hampton and Roy 2002).…”
Section: Literature and Theory Guiding The Studymentioning
confidence: 99%
“…Even though I have been working with Indigenous peoples for several years, it was still important to consider whether I had "the cultural knowledge to accurately interpret and validate the experiences…within the context of the phenomenon under study" (Tillman, 2002, p. 4). Juntunen et al (2001) and Browne and Varcoe (2006) cautioned that the topic may be misunderstood by the majority culture when conducting research with participants from another culture. In this study, it is possible that I may have unconsciously interjected my bias into the data analysis and study method.…”
Section: Sampling In Order To Obtain An Appropriate Amount Of Data Tmentioning
confidence: 99%
“…Other researchers found that students described success as discovering self, and being able to help others in their community (Bowman, 2013;Juntunen et al, 2001;Villegas, 2009 Māori nursing students in New Zealand, with a focus on recruitment and retention. In addition to several of the above mentioned barriers, they also identified family commitments as adding tension to the educational process, making it difficult for students to choose between family needs and academic requirements (Wilson et al).…”
Section: Descriptions Of Successmentioning
confidence: 99%
See 1 more Smart Citation